Solid-Supported Heterogenized Palladium Nanoparticles: Propitious Vehicles for Sonogashira Cross-Coupling Reaction - Srivastava A.; Avasthi N.; Anand S.; Yadav D.; Rangarajan T.M.; Pasricha S. (My University, 2025)
[No abstract available]